circEPS15 Overexpression in Hepatocellular Carcinoma Modulates Tumor Invasion and Migration - Jiang, Bin; Tian, Maolin; Li, Gang; Sadula, Abuduhaibaier; Xiu, Dianrong; Yuan, Chunhui; Bing, Yuntao (Frontiers in Genetics, 2022)
Background: Hepatocellular carcinoma (HCC) is one kind of the leading causes of cancer-related deaths in the world. Recent evidence indicates that circular RNAs (circRNAs) play important roles in tissue development, gene transcription, signal regulation and tumorigenesis. However, whether circRNAs are involved in HCC progression and encode functional proteins remains largely unknown. Methods: circRNAs microarrays were performed using pathologically diagnosed HCC samples and paired adjacent normal liver tissues. Cell invasion, migration, cycle, and apoptosis post circRNA overexpression were measured using a transwell culture system, a wound healing assay, and flow cytometry. Full-length, mutated, and truncated sequences of circEPS15 with a FLAG tag were inserted into a circular expression vector. Western blotting was used to confirm circEPS15 expression and the requirement of internal ribosomal entry site (IRES) elements within the circRNA. The miRNA and mRNA expression profiles were obtained by analyzing data retrieved from The Cancer Genome Atlas (TCGA) database. We then constructed a ceRNA network ofcircEPS15, miRNAs, and mRNAs. Results: The expression of circEPS15 was downregulated in HCC tissues, and the survival curves showed that low circEPS15 levels were associated with poor overall survival in HCC patients. Overexpression of circEPS15 suppressed tumor invasion and migration by inhibiting the TJP1/CDH2/VIM signaling pathway and retarded cell cycle progression, yet had no effect on cell apoptosis. ceRNA analysis and qRT-PCR results suggest a possible circRNA (circEPS15)-miRNA-mRNA network in HCC. The spanning junction open reading frame in circEPS15 driven by IRES encoded a novel protein. Conclusions: Endogenous circEPS15 plays a novel role in repressing HCC through the ceRNA network and encoding a functional protein.